Effect of Enzogenol® Supplementation on Cognitive, Executive, and Vestibular/Balance Functioning in Chronic Phase of Concussion. Issue 1 (17th February 2017) - Walter, A.; Finelli, K.; Bai, X.; Arnett, P.; Bream, T.; Seidenberg, P.; Lynch, S.; Johnson, B.; Slobounov, S.
ABSTRACT: This study examined the feasibility of Enzogenol® as a potential treatment modality for concussed individuals with residual symptoms in the chronic phase. Forty-two student-athletes with history of sport-related concussion were enrolled, comparing Enzogenol® versus placebo. Testing was conducted using virtual reality (VR) and electroencephalography (EEG), with neuropsychological (NP) tasks primarily used to induce cognitive challenges. After six weeks, the Enzogenol® group showed enhanced frontal-midline theta, and decreased parietal theta power, indicating reduced mental fatigue. Subjects enrolled in the Enzogenol® group also self-reported reduced mental fatigue and sleep problems. This suggests that Enzogenol® has the potential to improve brain functioning in the chronic phase of concussion.